Studies of Interaction of Two Common Drugs and DNA in the Presence of Neutral Red by Fluorescence Spectroscopy and RLS Spectroscopy Method - Yan, Miaomiao; Wei, Guangcheng (Asian Journal of Chemistry, 2012)
Detailed analyses of the interaction of drugs (cefoperazone and acheomycin) with DNA by fluorescence, resonance light scattering spectroscopic techniques are carried out in this work. All the evidences show that the cefoperazone and acheomycin both can affect the fluorescence of neutral red-DNA system. Cefoperazone and acheomycin obviously can quench the resonance light scattering spectrum of neutral red-DNA system, it indicates that the drugs can combing with DNA and damage the long distance assembly of neutral red in the DNA surface. The binding mode of acheomycin and DNA is complicated than cefoperazone.